Response to volume resuscitation in children with severe malaria. - Maitland, K; Pamba, A; Newton, C; Levin, M (2003)
OBJECTIVES: To examine whether hypovolemia is an important cause of the acidosis in children with severe malaria. DESIGN: Prospective phase 1 study examining the safety of volume expansion using detailed hemodynamic monitoring. SETTING: High-dependency unit of Kilifi District Hospital on the coast of Kenya. PATIENTS: Kenyan children admitted with clinical features of severe malaria (impaired consciousness or deep breathing) complicated by acidosis (base excess of less than -8). Three groups were considered: severe malarial anemia plus acidosis if hemoglobin of <5 mg/dL and base excess less than -8; moderate malaria acidosis if the base excess was between -8 and -15; severe malaria acidosis if the base excess was less than -15. INTERVENTIONS: Patients received between 10 and 40 mL/kg of either 0.9% normal saline or 4.5% human albumin solution. MEASUREMENTS AND MAIN RESULTS: A total of 53 children were recruited, and all had evidence of compensated shock at admission, with tachycardia, tachypnea, and prolonged capillary refill time. Mean central venous pressure (se) at admission was 2.9 cm H(2)O (0.5 cm H(2)O); in the severe malaria acidosis group, 44% had hypotension (systolic blood pressure of <80 mm Hg). Improvements of hemodynamic indices and a reduction in acidosis followed administration of either saline or albumin. By 8 hrs, mean central venous pressure had increased to 7.5 cm H(2)O (0.5 cm H(2)O, F = 34.4, p <.001) and was associated with a reduction in mean respiratory rate from 49 to 41 breaths/min (2 to 1 breaths/min, respectively; F = 7.0; p =.009), a reduction in tachycardia from 151 to 141 beats/min (5 to 3 beats/min, respectively; F = 3.4; p =.06), and a reduction in capillary refill time. No child developed evidence of the life threatening complications of pulmonary edema and increased intracranial pressure. CONCLUSIONS: Volume depletion is present at admission in the majority of children with severe malaria complicated by acidosis. Volume expansion corrects the hemodynamic abnormalities and is associated with improved organ function and reduction in acidosis. Formal trials of volume expansion are needed to determine whether volume expansion will reduce mortality.